Factors associated with vitamin B12 deficiency in adults attending tertiary care Hospital in Vadodara: a case control study - Sangita V. Patel; Alpesh B. Makwana; Archana U. Gandhi; Greenam Tarani; Jesal Patel; Vipul Bhavsar (SpringerOpen, 2022)
Abstract Background In India, approximately 75% of population that is over 650 million people have B12 deficiency majority of which is caused by variation in demography, diet, and religion. Conditions such as smoking, alcohol, and antacid use are certain causes for incidence of vitamin B12 deficiency. Looking at various adverse health effects of drinking demineralized water, there is possibility that it may also be one of the newly associated factors for increasing incidence and prevalence of vitamin B12 deficiency. Objective To assess the risk factors associated with vitamin B12 deficiency. Methods A case control study was conducted at SSG Hospital in Vadodara, Gujarat, wherein all the patients visiting the hospital from November 2017 to June 2018 with symptoms suggestive of B12 deficiency and serum B12 level below 200pg/mL were included in the study. Information regarding the vitamin B12 deficiency was obtained from the patients. Controls were selected and matched with cases as per age group to minimize confounding. Results Our study showed statistically significant association of vegetarian diet (p value=0.0027, OR=2.00) (odds ratio), dark complexion (0.0069, OR=2.53), socio economic status (p value= 0.0001), and use of RO (reverse osmosis) water (p value=0.0099, OR=3.61) with vitamin B12 deficiency at 95% CI (confidence interval). Conclusion Independent association between use of R.O. water, vegetarian diet, socio economic class, and dark complexion with vitamin B12 deficiency.